2008
DOI: 10.1007/s11524-008-9255-1
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Availability and Neighborhood Characteristics in Los Angeles, California and Southern Louisiana

Abstract: The objective of this study was to examine the associations between alcohol availability types and community characteristics in randomly selected census tracts in Southern California and Southeastern Louisiana. Outlet shelf space and price by beverage type was collected from all off-sale alcohol outlets in 189 census tracts by trained research personnel. Three aspects of alcohol availability at the census tract level were considered-outlets per roadway mile, shelf space, and least price by beverage type. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 45 publications
2
51
1
Order By: Relevance
“…Malt liquor is readily available and heavily promoted in many poor, inner-city neighborhoods. Bluthenthal et al (2008) found a positive association between retail shelf space devoted to malt liquor and poverty in retail outlets in Los Angeles and southeastern Louisiana. Jones-Webb et al (2008) observed that malt liquor ads accounted for a third of all storefront advertising on alcohol outlets in poor neighborhoods in 10 U.S. cities. Malt liquor consumption is associated with several troublesome drinking patterns that may contribute to neighborhood problems, including frequent and heavy drinking, rapid consumption, drinking outdoors, and drinking in the morning or afternoon (Bluthenthal, Brown-Taylor, Guzman-Becerra, & Robinson, 2005;Bradizza, Collins, Vincent & Falco, 2006;Chen & Paschall, 2003;Vilamovska, Brown-Taylor, & Bluthenthal, 2009).…”
Section: Introduction Malt Liquor Consumption and Related Problemsmentioning
confidence: 90%
See 1 more Smart Citation
“…Malt liquor is readily available and heavily promoted in many poor, inner-city neighborhoods. Bluthenthal et al (2008) found a positive association between retail shelf space devoted to malt liquor and poverty in retail outlets in Los Angeles and southeastern Louisiana. Jones-Webb et al (2008) observed that malt liquor ads accounted for a third of all storefront advertising on alcohol outlets in poor neighborhoods in 10 U.S. cities. Malt liquor consumption is associated with several troublesome drinking patterns that may contribute to neighborhood problems, including frequent and heavy drinking, rapid consumption, drinking outdoors, and drinking in the morning or afternoon (Bluthenthal, Brown-Taylor, Guzman-Becerra, & Robinson, 2005;Bradizza, Collins, Vincent & Falco, 2006;Chen & Paschall, 2003;Vilamovska, Brown-Taylor, & Bluthenthal, 2009).…”
Section: Introduction Malt Liquor Consumption and Related Problemsmentioning
confidence: 90%
“…Malt liquor is distinguished from regular beer by its higher alcohol content, lower price, and larger typical container sizes, including the 40-ounce bottle (Bluthenthal et al, 2008;Jones-Webb et al, 2008;U.S. Department of Health and Human Services, 2008).…”
Section: Introduction Malt Liquor Consumption and Related Problemsmentioning
confidence: 99%
“…Disadvantaged areas, particularly those in the inner city, may also have other factors that increase substance abuse, such as numerous alcohol outlets and open illegal drug scenes (Bluthenthal et al, 2008).…”
Section: Two Emerging Traditions Of Area-based Substance Use Studiesmentioning
confidence: 99%
“…Contextual factors such as drinking norms and the availability of alcohol in the environment can also infl uence the extent to which individuals drink alcohol in response to stress (e.g., Herd, 1994;Huckle et al, 2008;Lindenberg et al, 1999;Scribner et al, 2000). Importantly, racial/ethnic minorities and low-income persons are more likely to reside in communities with more alcohol outlets and aggressive alcohol advertising (Bluthenthal et al, 2008;Pollack et al, 2005), and have been shown to have fewer stressbuffering and coping resources (Meyer et al, 2008;Pearlin et al, 1981;Thoits, 1995). These groups might, therefore, be more negatively affected by experiences of social adversity and psychological stress.…”
Section: The Question Of Differential Vulnerabilitymentioning
confidence: 99%